Schlaf gut! - Nuku hyvin! Zur Versprachlichung der Trauer auf Tierfriedhöfen. Ein deutsch-finnischer Vergleich - Wagner Doris (Société Néophilologique de Helsinki, 2025)
In today’s society, the relationship between humans and animals is constantly changing. This shift, often referred to as the ‘animal turn’, started in the 1970s and has led to a paradigm shift: animals are seen as individuals, as subjects rather than objects. Until recently, pet cemeteries have been primarily studied from within theological, cultural, and sociological frameworks. Language, however, has only been scarcely examined, if at all. Pet cemeteries are places where foreign languages are used, and the study looks at the manifestations and origins of these languages. A comparison of inscriptions from the cemeteries showed that mourning is expressed in a much more emotional way in a German cemetery (here: Saarbrücken) than in a cemetery in Finland (here: Turku), where mourning is more reserved. The number of texts in the Turku cemetery is significantly lower than the number of inscriptions in Saarbrücken. In addition to examining the verbalization of mourning, this study offers other interesting issues to be explored: language diversity on pet gravestone inscriptions, dialectal variation, pet names and regional differences among pet gravestones within both countries.